2023
DOI: 10.1111/joor.13523
|View full text |Cite
|
Sign up to set email alerts
|

Fifty years of development of neuroscientific insights into oro‐facial pain and its control

Abstract: When the Journal of Oral Rehabilitation was established in 1973, there was very limited understanding of the mechanisms underlying neurally based functions, including those unique to the face, mouth and jaws (e.g. dental pain, taste, chewing, swallowing and salivation). Since that time, technological and other advances have led to new insights into the structure, connectivity and function of cranial nerves and areas of the central nervous system (CNS) involved in oro-facial functions and disorders or related f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 115 publications
0
6
0
Order By: Relevance
“…There are several possible mechanisms for the relationship between swallowing function and dementia. Swallowing actions activate brain function and improve learning and memory skills 24 , 25 . It was also reported that swallowing actions increase cerebral blood flow and the partial pressure of oxygen in the brain 26 .…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible mechanisms for the relationship between swallowing function and dementia. Swallowing actions activate brain function and improve learning and memory skills 24 , 25 . It was also reported that swallowing actions increase cerebral blood flow and the partial pressure of oxygen in the brain 26 .…”
Section: Discussionmentioning
confidence: 99%
“…From here, the signals are passed to motoneurons in the brainstem motor nuclei (e.g. trigeminal motor nucleus) and to neurons in nociceptive circuits and pathways in brainstem and higher areas of the CNS comparable to those noted above for spinal nociceptive signals ( Sessle, 2006 , Chichorro et al, 2017 , Shinoda et al, 2019 , Chung et al, 2020 , Sessle, 2023 ). And like the spinal sensorimotor system, these nociceptive circuits and pathways are subject to descending modulation from higher CNS areas, sex differences exist in some of their features, and the pathways and circuits may express plastic changes following noxious stimulation or other peripheral manipulations (e.g.…”
Section: Pain and Sensorimotor Interactionsmentioning
confidence: 96%
“…And like the spinal sensorimotor system, these nociceptive circuits and pathways are subject to descending modulation from higher CNS areas, sex differences exist in some of their features, and the pathways and circuits may express plastic changes following noxious stimulation or other peripheral manipulations (e.g. trimming or extraction of teeth, nerve injury) and in association with the acquisition of novel sensorimotor skills ( Cairns, 2007 , Avivi-Arber et al, 2011 , Arce-McShane et al, 2014 , Cairns et al, 2014 , Chichorro et al, 2017 , Avivi-Arber and Sessle, 2018 , Yao and Sessle, 2018 , Shinoda et al, 2019 , Chung et al, 2020 , Tashiro and Bereiter, 2020 , Sessle, 2021 , Sessle, 2023 ). Furthermore, like the spinal sensorimotor system, the pain-related plastic changes in the CNS may result in altered sensorimotor behavior through changes to descending pathways such as those from SI and MI that influence brainstem motoneurons and/or through changes to descending pathways contributing to the modulation of central sensitization processes of nociceptive circuits within the trigeminal brainstem sensory nuclear complex and which can influence trigeminal motoneuron activity ( Sessle, 2006 , Sessle, 2011a , Chichorro et al, 2017 , Avivi-Arber and Sessle, 2018 , Shinoda et al, 2019 ).…”
Section: Pain and Sensorimotor Interactionsmentioning
confidence: 99%
See 2 more Smart Citations